Pre-exercise carbohydrate status and immune responses to prolonged cycling: II. Effect on plasma cytokine concentration - Bishop, N. C.; Walsh, N. P.; Haines, D. L.; Richards, E. E.; Gleeson, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
Ingesting carbohydrate (CHO) beverages during heavy exercise is associated with smaller changes in the plasma concentrations of several cytokines. The influence of dietary CHO availability on these responses has not been determined. Therefore, the present study investigated the influence of pre-exercise CHO status on plasma interleukin (IL)-6, IL-10, and IL-1 receptor antagonist (IL-1ra) responses to prolonged cycling. Seven trained male cyclists performed a glycogen-lowering bout of cycling and were randomly assigned to follow a diet ensuring either greater than 70% (HIGH) or less than 10% (LOW) of daily energy intake from CHO for the next 3 days. On day 4 subjects performed an exercise test that comprised cycling for 1 hour at 60% Wmax immediately followed by a time-trial (TT) ensuring an energy expenditure equivalent to cycling for 30 min at 80% Wmax. Subjects repeated the protocol after 7 days, this time following the second diet. The order of the trials was counterbalanced. At 1 and 2 hours post-TT, plasma concentrations of IL-6 and IL-10 were 2-fold greater on the LOW trial than on the HIGH trial, and peak plasma concentrations of IL-1ra were 9-fold greater on the LOW trial than on the HIGH trial. These findings suggest that pre-exercise CHO status can influence the plasma cytokine response to prolonged cycling.